A Brief Review of Miserite Glass-Ceramics. Issue 4 (2nd October 2018) - Muhammed, Fenik Kaml; Pollington, Sarah; Liu, Yi
ABSTRACT: The aim is focused on an overview of the miserite and analyzing factors affecting the miserite glass-ceramics (GC) and its structures. Many chemical formulae have been used based on varying chemical criteria, and several attempts have been made to fabricate different variations of miserite GC. An electronic search has been conducted across Ovid Medline, complemented by a manual search across individual databases, such as Cochrane, Web of Science databases and Google Scholar for the purpose of literature analysis on the mentioned topic. The studies have been reviewed and compared. This article summarizes the current scientific studies through a brief review of the structural and behavioral features of the miserite, followed by a detailed description of the miserite GC that has been manufactured. Based on previous findings, it can be concluded that miserite GC exhibits good chemical solubility, machinability, high biaxial flexural strength and fracture toughness. Miserite GC has promising applications in biomedical field. The advantages of miserite GC require extensive investigation in order to fulfill the knowledge gaps surrounding the development of the GCs. There is still a lack of research about miserite GC regarding potential clinical applications. GRAPHICAL ABSTRACT: